APG Marketing and Management Sdn Bhd / Muhammad Aiman Rozelan - Rozelan, Muhammad Aiman (Faculty of Business and Management, 2023)
Primarily, this report will be discussed regarding on m y internship experience at APG Marketing & Management Sdn Bhd. In brief, this extensive report will begin with an overview of Student Curricular Vitae and a synopsis of company history. This will be followed by APG Marketing & Management's corporate culture, which includes the company's goal and mission as w ell as the products and services it offers. Along m y internship journey, I worked mostly in the Administration Department, which was consistent with the course I completed at UiTM Melaka. I will be revealed about m y experiences while working as a trainee Administration. I had the chance to learn m any things from them, including how to manage administration in the actual world rather than only in theory as I had done in the past through lectures. The major purpose of this academic internship is to better understand the theories, ideas, and practices of discipline or major by actively engaging in a "hands-on," work-based, learning experience. APG Marketing & Management SWOT analysis's will be covered thoroughly in this study.